DIVIDENS, STOCK REPURCHASES AND VALUE OF THE FIRM - R. AGUS SARTONO; TURYASNGURA WILBERFORCE (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 1999)
Firms that wish to distribute excess cash relative to profitable investmentopportunities, choose between paying large dividends and stock repurchase. The latter can also be debt financed thus increasing the financial leverage of the firm. Both actions have an impact on the stock price, and by implication, on the value of the firm. This paper examines both the dividend option and the repurchase option. Therefore this research also demonstrates that: (a) Under a stable tax regime, investors prefer stock repurchases to large dividends and (b) Under a debt financed stock repurchase, a minimum amount of stock must tee repurchased to avoid a drop in the stock price.